2009
DOI: 10.1007/s10709-009-9420-9
|View full text |Cite
|
Sign up to set email alerts
|

B-chromosome frequency stability in Prochilodus lineatus (Characiformes, Prochilodontidae)

Abstract: The genus Prochilodus includes individuals ranging in size from medium to large, being highly relevant for commercial and subsistence fishing. Prochilodus species have a diploid number of 2n = 54 chromosomes and up to seven supernumerary (B) microchromosomes. Previous research has shown that B frequency increased drastically in the Mogi-Guaçu river population of Prochilodus lineatus in the early 1980s, whereas it remained about constant in the 1990s. Here we analyses B frequency in this population during the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…These data are consistent with those described by Cavallaro et al [2000], Oliveira et al [1997], and Voltolin et al [2009], who studied B chromosomes in P. lineatus from the Mogi-Guaçu River and suggested a stable frequency ( table 1 ). In contrast, intraindividual variation was not found in our study, as was previously proposed by Oliveira et al [1997] and Cavallaro et al [2000] and confirmed by Voltolin et al [2010b]. Nevertheless, the stabilization of B chromosome frequencies in P. lineatus does not apply to all the variant forms.…”
Section: Resultssupporting
confidence: 73%
“…These data are consistent with those described by Cavallaro et al [2000], Oliveira et al [1997], and Voltolin et al [2009], who studied B chromosomes in P. lineatus from the Mogi-Guaçu River and suggested a stable frequency ( table 1 ). In contrast, intraindividual variation was not found in our study, as was previously proposed by Oliveira et al [1997] and Cavallaro et al [2000] and confirmed by Voltolin et al [2010b]. Nevertheless, the stabilization of B chromosome frequencies in P. lineatus does not apply to all the variant forms.…”
Section: Resultssupporting
confidence: 73%
“…To date, the cytogenetic data of Neotropical fishes have shown some major trends: karyotypic stability in Anostomidae [ 57 , 58 ], Prochilodontidae [ 58 , 59 61 ], and Curimatidae [ 57 , 62 ], and the existence of species complexes in the genera Astyanax [ 63 ] and Hoplias [ 64 ]. However, the cytogenetic pattern observed in bryconine from Brazilian southeastern coastal basins represents the first case in which synapomorphies of chromosomal banding show monophyly of well-defined morphological species.…”
Section: Discussionmentioning
confidence: 99%
“…In fish, the possibility of neutralization through mitotic stabilization of B-chromosomes was also observed in Prochilodus lineatus , in the population from the Mogi-Guaçu River (Brazil) ( Oliveira et al 1997 ). Afterwards, in this same population, Cavallaro et al (2000) found a drastic temporal decline in the degree of B mitotic instability; Voltolin et al (2010) showed that the stabilization process was continuous for over 15 years; and currently, the population of Prochilodus lineatus from the Mogi-Guaçu River presents a total mitotic stability index (MI = 0) and the B chromosomes were considered completely neutralized.…”
Section: Resultsmentioning
confidence: 89%